Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Let's solve the given problem thoroughly and step by step to determine which of the given expressions are equivalent to the expression:
[tex]\[ 5 \log_{10} x + \log_{10} 20 - \log_{10} 10 \][/tex]
### Step 1: Simplify the given expression
We start with the given expression:
[tex]\[ 5 \log_{10} x + \log_{10} 20 - \log_{10} 10 \][/tex]
Using the properties of logarithms:
[tex]\[ \log_b (mn) = \log_b m + \log_b n \][/tex]
[tex]\[ \log_b \left(\frac{m}{n}\right) = \log_b m - \log_b n \][/tex]
[tex]\[ \log_b (m^n) = n \log_b m \][/tex]
First, note that [tex]\(\log_{10} 10 = 1\)[/tex], so the expression simplifies as follows:
[tex]\[ 5 \log_{10} x + \log_{10} 20 - 1 \][/tex]
Next, rewrite [tex]\(\log_{10} 20\)[/tex]:
[tex]\[ \log_{10} 20 = \log_{10} (2 \cdot 10) = \log_{10} 2 + \log_{10} 10 = \log_{10} 2 + 1 \][/tex]
Replace this in the simplified expression:
[tex]\[ 5 \log_{10} x + (\log_{10} 2 + 1) - 1 \][/tex]
[tex]\[ 5 \log_{10} x + \log_{10} 2 \][/tex]
The final simplified form is:
[tex]\[ 5 \log_{10} x + \log_{10} 2 \][/tex]
### Step 2: Rewrite using logarithmic properties
Using the logarithmic property [tex]\(\log_b (mn) = \log_b m + \log_b n\)[/tex], we combine the two logarithms:
[tex]\[ 5 \log_{10} x + \log_{10} 2 = \log_{10} (x^5) + \log_{10} 2 = \log_{10} (2 x^5) \][/tex]
So, our given expression is equivalent to:
[tex]\[ \log_{10} (2 x^5) \][/tex]
### Step 3: Check all given expressions
- Expression 1: [tex]\(\log_{10} (2 x^5)\)[/tex]
This matches exactly with our simplified form above. So, this is indeed equivalent.
- Expression 2: [tex]\(\log_{10} (20 x^5) - 1\)[/tex]
Rewrite [tex]\(\log_{10} (20 x^5)\)[/tex]:
[tex]\[ \log_{10} (20 x^5) = \log_{10} (20) + \log_{10} (x^5) = \log_{10} 20 + 5 \log_{10} x \][/tex]
Using [tex]\(\log_{10} 20 = \log_{10} (2 \cdot 10) = \log_{10} 2 + \log_{10} 10 = \log_{10} 2 + 1\)[/tex], we get:
[tex]\[ \log_{10} (20 x^5) = (\log_{10} 2 + 1) + 5 \log_{10} x = \log_{10} 2 + 5 \log_{10} x + 1 \][/tex]
Subtracting 1:
[tex]\[ \log_{10} 2 + 5 \log_{10} x + 1 - 1 = \log_{10} 2 + 5 \log_{10} x \][/tex]
Which is equal to:
[tex]\[ 5 \log_{10} x + \log_{10} 2 \][/tex]
This matches our simplified form, so it is also equivalent.
- Expression 3: [tex]\(\log_{10} (100 x) + 1\)[/tex]
Rewrite [tex]\(\log_{10} (100 x)\)[/tex]:
[tex]\[ \log_{10} (100 x) = \log_{10} 100 + \log_{10} x = 2 + \log_{10} x \][/tex]
Adding 1:
[tex]\[ 2 + \log_{10} x + 1 = 3 + \log_{10} x \][/tex]
This does not match our simplified form, so it is not equivalent.
- Expression 4: [tex]\(\log_{10} (2 x)^5\)[/tex]
Using the logarithmic property:
[tex]\[ \log_{10} (2 x)^5 = 5 \log_{10} (2 x) = 5 (\log_{10} 2 + \log_{10} x) = 5 \log_{10} 2 + 5 \log_{10} x \][/tex]
This does not match our simplified form, so it is not equivalent.
- Expression 5: [tex]\(\log_{10} (10 x)\)[/tex]
Rewrite [tex]\(\log_{10} (10 x)\)[/tex]:
[tex]\[ \log_{10} (10 x) = \log_{10} 10 + \log_{10} x = 1 + \log_{10} x \][/tex]
This does not match our simplified form, so it is not equivalent.
### Final Answer
The equivalent expressions to the given expression are:
1. [tex]\(\log_{10} (2 x^5)\)[/tex]
2. [tex]\(\log_{10} (20 x^5) - 1\)[/tex]
[tex]\[ 5 \log_{10} x + \log_{10} 20 - \log_{10} 10 \][/tex]
### Step 1: Simplify the given expression
We start with the given expression:
[tex]\[ 5 \log_{10} x + \log_{10} 20 - \log_{10} 10 \][/tex]
Using the properties of logarithms:
[tex]\[ \log_b (mn) = \log_b m + \log_b n \][/tex]
[tex]\[ \log_b \left(\frac{m}{n}\right) = \log_b m - \log_b n \][/tex]
[tex]\[ \log_b (m^n) = n \log_b m \][/tex]
First, note that [tex]\(\log_{10} 10 = 1\)[/tex], so the expression simplifies as follows:
[tex]\[ 5 \log_{10} x + \log_{10} 20 - 1 \][/tex]
Next, rewrite [tex]\(\log_{10} 20\)[/tex]:
[tex]\[ \log_{10} 20 = \log_{10} (2 \cdot 10) = \log_{10} 2 + \log_{10} 10 = \log_{10} 2 + 1 \][/tex]
Replace this in the simplified expression:
[tex]\[ 5 \log_{10} x + (\log_{10} 2 + 1) - 1 \][/tex]
[tex]\[ 5 \log_{10} x + \log_{10} 2 \][/tex]
The final simplified form is:
[tex]\[ 5 \log_{10} x + \log_{10} 2 \][/tex]
### Step 2: Rewrite using logarithmic properties
Using the logarithmic property [tex]\(\log_b (mn) = \log_b m + \log_b n\)[/tex], we combine the two logarithms:
[tex]\[ 5 \log_{10} x + \log_{10} 2 = \log_{10} (x^5) + \log_{10} 2 = \log_{10} (2 x^5) \][/tex]
So, our given expression is equivalent to:
[tex]\[ \log_{10} (2 x^5) \][/tex]
### Step 3: Check all given expressions
- Expression 1: [tex]\(\log_{10} (2 x^5)\)[/tex]
This matches exactly with our simplified form above. So, this is indeed equivalent.
- Expression 2: [tex]\(\log_{10} (20 x^5) - 1\)[/tex]
Rewrite [tex]\(\log_{10} (20 x^5)\)[/tex]:
[tex]\[ \log_{10} (20 x^5) = \log_{10} (20) + \log_{10} (x^5) = \log_{10} 20 + 5 \log_{10} x \][/tex]
Using [tex]\(\log_{10} 20 = \log_{10} (2 \cdot 10) = \log_{10} 2 + \log_{10} 10 = \log_{10} 2 + 1\)[/tex], we get:
[tex]\[ \log_{10} (20 x^5) = (\log_{10} 2 + 1) + 5 \log_{10} x = \log_{10} 2 + 5 \log_{10} x + 1 \][/tex]
Subtracting 1:
[tex]\[ \log_{10} 2 + 5 \log_{10} x + 1 - 1 = \log_{10} 2 + 5 \log_{10} x \][/tex]
Which is equal to:
[tex]\[ 5 \log_{10} x + \log_{10} 2 \][/tex]
This matches our simplified form, so it is also equivalent.
- Expression 3: [tex]\(\log_{10} (100 x) + 1\)[/tex]
Rewrite [tex]\(\log_{10} (100 x)\)[/tex]:
[tex]\[ \log_{10} (100 x) = \log_{10} 100 + \log_{10} x = 2 + \log_{10} x \][/tex]
Adding 1:
[tex]\[ 2 + \log_{10} x + 1 = 3 + \log_{10} x \][/tex]
This does not match our simplified form, so it is not equivalent.
- Expression 4: [tex]\(\log_{10} (2 x)^5\)[/tex]
Using the logarithmic property:
[tex]\[ \log_{10} (2 x)^5 = 5 \log_{10} (2 x) = 5 (\log_{10} 2 + \log_{10} x) = 5 \log_{10} 2 + 5 \log_{10} x \][/tex]
This does not match our simplified form, so it is not equivalent.
- Expression 5: [tex]\(\log_{10} (10 x)\)[/tex]
Rewrite [tex]\(\log_{10} (10 x)\)[/tex]:
[tex]\[ \log_{10} (10 x) = \log_{10} 10 + \log_{10} x = 1 + \log_{10} x \][/tex]
This does not match our simplified form, so it is not equivalent.
### Final Answer
The equivalent expressions to the given expression are:
1. [tex]\(\log_{10} (2 x^5)\)[/tex]
2. [tex]\(\log_{10} (20 x^5) - 1\)[/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.